153 Differences in Health and Carcass Characteristics of Yearling Steers That Received Free-choice Garlic-infused Mineral Supplements. (8th October 2021) - Cheang-Deis, Iris Ho In; Oyedeji, Oluwatobi; Block, Hushton; Rochon, Kateryn; Asai-Coakwell, Mika; Erickson, Nathan; Lardner, Herbert; Durunna, Obioha N
Abstract: Garlic products have been reported to have antimicrobial effects and may trigger anemia in horses, but their direct impact on feedlot cattle has not been detailed. With increased free-choice feeding of garlic-infused mineral supplements to beef cattle, it is important to evaluate this strategy's impact on the animals' health and the potential impact on carcass qualities. This 2-yr study recruited 208 crossbred feedlot steers in a supplementation trial using a completely randomized design. Each year, 104 steers were assigned to 1 of 4 groups that received either non-garlic mineral supplement (MS), MS + 0.3% garlic-oil-based premix (GOil), MS + 2.5% garlic powder (LGP), MS + 5% garlic powder (HGP). Feed and supplements were provided on an ad-lib basis and were measured for each steer with automatic feeding units. The study evaluated health indicators such as blood parameters and internal parasites. At harvest, carcass characteristics (including the incidence of liver abscesses) were assessed for all steers. The groups consumed between 156 and 208 g/d of the supplement over the two years, with the MS group having a lower overall supplement intake than other groups. The average daily consumption of garlic products in GOil, LGP, and HGP were approximately 0.6g/d, 5.2g/d, and 10.1g/d, respectively. There was no difference in total fecal egg counts (P = 0.45) among the groups. There was no association between the treatment groups and incidences of liver abscess scores (P = 0.10) nor carcass grade outcomes (P = 0.84). Further, there were no differences in hot carcass weight (P = 0.90), rib eye area (P = 0.34) and carcass backfat thickness (P = 0.99). All blood parameters evaluated were within normal ranges for all groups. The results suggest that infusing commercial garlic products into mineral supplements is not associated with undesirable effects on cattle health or carcass characteristics.